PENGARUH PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KARYAWAN PADA BPJS KETENAGAKERJAAN CABANG PALEMBANG - Muhammad Ridwan; . Noviarni; Ratih Hardianti (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
The research basically discusses the effect of Career Training and Development on employee Productivity at the Palembang Social Security Agency (BPJS) Branch. This study uses a correlation coefficient analysis, determination, and hypothesis testing partially and simultaneously. The sample of this study used a saturated sample of 45 people who were employees of the Employment Social Security Agency (BPJS) Palembang Branch.From the results of research between training (X1) and career development (X2) on employee productivity (Y) the value of correlation (R) is 0.685 because the value of multiple correlation is in the range 0.600 - 0.799, meaning that there is a positive relationship between training (X1 ) and career development (X2) together towards employee productivity (Y), where the equation obtained from the results of multiple linear regression is Y = 4.176 + 0.193 X1 + 0.899 X2 + e. The coefficient of determination (R2) is 0.470 or equal to 47%, which means that 47% of employee job satisfaction is influenced by career training and development. While the remaining 53%. influenced by other factors not examined in this study, such as work environment, education, income, social security, employment opportunities, capacity building, and production facilities. The results of the F test show the influence of career training and development on employee productivity at the Palembang Social Security Agency (BPJS) Branch. The results of the t-test of Training have an effect on employee productivity at the Palembang Branch of the Social Security Agency (BPJS) and career development has an effect on Employee Productivity at the Palembang Social Security Agency (BPJS) of the Palembang Branch.Keywords: Productivity, Training and Career Development.